1993
DOI: 10.1093/geronj/48.4.p157
|View full text |Cite
|
Sign up to set email alerts
|

Facts and Fiction About Memory Aging: A Quantitative Integration of Research Findings

Abstract: A meta-analytic literature review on adult age differences in speed of search in short-term memory (12 studies), memory span (40 studies), list recall (68 studies), paired-associate recall (21 studies), and prose recall (39 studies) is presented. Results show that age differences are quite large (depending on the task, elderly people can be situated between the 3rd and the 38th percentile of the adult age memory performance distribution) and quasi-omnipresent, even under conditions of cued recall or semantic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
216
2
4

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(236 citation statements)
references
References 0 publications
14
216
2
4
Order By: Relevance
“…The associations between age and regional volumes follow the pattern observed in previous reports, although the correlation between age and HC volume (especially at follow-up) is somewhat larger than the reported median (for review, see Raz, 2000). The magnitude of age-related memory differences are in the typical range reported in the literature (Verhaeghen et al, 1993).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The associations between age and regional volumes follow the pattern observed in previous reports, although the correlation between age and HC volume (especially at follow-up) is somewhat larger than the reported median (for review, see Raz, 2000). The magnitude of age-related memory differences are in the typical range reported in the literature (Verhaeghen et al, 1993).…”
Section: Resultssupporting
confidence: 54%
“…Age-related declines in episodic memory are common (Verhaeghen et al, 1993), but their neuroanatomical underpinnings are unclear. Aging differentially affects the putative brain substrates of memory: the hippocampus (HC), the entorhinal cortex (EC), and the prefrontal cortex (PFC) (Squire and Zola-Morgan, 1991;Buckner, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Three other meta-analytic reviews have revealed that (expressed as the standardized differences between younger and older groups) mean age effects for free recall were Ϫ.97 (La Voie & Light, 1994), -.99 (Verhaeghen, Marcoen, & Goossens, 1993), and Ϫ1.01 (Spencer & Raz, 1995). In the present study, the mean effect for free recall expressed as a standardized difference was Ϫ1.22.…”
Section: Pm Relative To Retrospective Memorysupporting
confidence: 50%
“…The hypothesis that aging leads to disproportionate declines in context processing was first formulated in the early 1980s (e.g., Burke & Light, 1981;Rabinowitz & Ackerman, 1982) and continues to be a central theme of research on cognitive aging (e.g., Braver et al, 2001). Age differences in memory tasks tend to increase as a function of the tasks' reliance on memory for contextual detail (for empirical and theoretical reviews, see Light, 1996;2000b;Spaniol & Bayen, 2004;Spencer & Raz, 1995;Verhaeghen, Marcoen, & Goossens, 1993;Zacks et al, 2000). Older adults' poor performance on tasks with high context reliance has been attributed to age deficits in specific cognitive processes such as self-initiated processing (e.g., Craik, 1986Craik, , 1994, recollection (e.g., Jacoby, 1999), or associative encoding (e.g., Naveh-Benjamin, 2000).…”
Section: Aging and Context Memorymentioning
confidence: 99%